Avtonomna dizrefleksija pri otrocih in mladostnikih z okvaro hrbtenjače - Bregant, Tina (Rehabilitacija (Ljubljana), 2016)
Abstract: We provide an overview of paediatric autonomic dysfunctions in children with spinal cord lesions. We present normal autonomic function as well as dysautonomy after spinal cord lesions. Special attention is paid to dysautonomy crisis % how to recognise and handle it. We present dysautonomy triggers and preventative procedures in order to avoid it, as avoidance of triggers as well as non-pharmalogical measures contribute most to the patient%s well-being. An episode of autonomic dysreflexia should not be overlooked because it represents a medical emergency. However, efficient recognition still represents a challenge. The reasons for that are various: from dysautonomy not being known, to difficulties children in reporting such events, as well as developmental issues, such as bowel and bladder control, which is not mastered till certain age. Developmental immaturity at the time of lesion turns rehabilitation into habilitation. We hope that this review is going to increase awareness of dysautonomy and hence contribute to a better health care of children with spinal cord lesions.
Keywords: Adolescent; Autonomic Dysreflexia; avtonomno živčevje; Child; mladostniki; otroci; poškodbe hrbtenjače; prevention and control